Education, Training and Policy - Selfe, P. L. (London : Hodder & Stoughton, 2000)
This textbook provides fresh and focussed coverage of the leading themes in this section of the sociology syllabus. It includes consensus, conflict, gender and education, ethnicity and education, training and recent legislation.
Includes bibliographical references and index.
Keywords: Educational sociology -- Great Britain; Education -- Great Britain -- Aims and objectives; Education and state -- Great Britain; Education